Experimental Evaluation of Nano-Enhanced Phase Change Materials in a Finned Storage Unit - Aichouni, M. A.; Alshammari, N. F.; Ben Khedher, N.; Aichouni, M. (Engineering, Technology & Applied Science Research, 2020)
The intermittent nature of renewable energy sources such as solar and wind necessitates integration with energy-storage units to enable realistic applications. In this study, thermal performance enhancement of the finned Cylindrical Thermal Energy Storage (C-TES) with nano-enhanced Phase Change Material (PCM) integrated with the water heating system under Storage, Charging and Discharging (SCD) conditions were investigated experimentally. The effects of the addition of copper oxide (CuO) and aluminum oxide (Al2O3) nanoparticles in PCM on thermal conductivity, specific heat, and on charging and discharging performance rates were theoretically and experimentally investigated and studied in detail. The experimental apparatus utilized paraffin wax as PCM, which was filled in Finned C-TES to conduct the experiments. The experimental results showed a positive improvement compared with the non-nano additive PCM. The significance and originality of this project lies within the evaluation and identification of preferable metal-oxides with higher potential for improving thermal performance.